Biodiesel as a pathway to economic empowerment: how renewable energy can alleviate poverty in developing regions / Shahida Hanum Kamarullah, Nur Sha’adah Zainuddin and Wan Noni Afida Ab Manan - Kamarullah, Shahida Hanum; Zainuddin, Nur Sha’adah; Ab Manan, Wan Noni Afida (Universiti Teknologi MARA, Negeri Sembilan, 2024)
A potential solution to the dual issues of energy sustainability and poverty reduction is biodiesel. Biodiesel is a renewable fuel that is derived from organic materials such as vegetable and animal fats. It is substantially less harmful than petroleum diesel, reducing greenhouse gas emissions by up to 78%. The reduction in emissions fosters environmental improvements in regions that significantly rely on diesel fuel and assist in combating climate change. Furthermore, by fostering local entrepreneurship and creating job opportunities, biodiesel manufacturing can contribute to economic growth in underdeveloped areas. The National Biodiesel Board estimates that the production of biodiesel creates $8 billion in wages annually and supports around 64,000 employments (National Biodiesel Board, 2022). Local communities in underdeveloped countries can improve their economic stability and access new revenue streams by establishing facilities for producing biodiesel. This change promotes long-term economic growth via local investment and business growth in addition to offering immediate employment opportunities. Therefore, biodiesel stands out as an achievable strategy for promoting local development and economic resilience in addition to providing sustainable energy and alleviating the widespread problem of poverty.